Navigating the real world: a grounded theory-based exploration of autistic adolescents identity formation in Marcelo in the real world - Yang, Shuo; Mani, Manimangai; Omar, Noritah (Academy Publication, 2023)
This study analyses the depiction of autism in Marcelo in the Real World, a young adult fiction novel, to critically explore the identity formation of the character Marcelo who navigates the challenges and complexities of the real world. By using the grounded theory and drawing on ideas from disability studies and social identity theory, the research demonstrates that parental guidance, encouragement and normal treatment of friends, and exposure to conflicts and contradictions are the most significant factors and can help autistic adolescents understand social life, improve social competence, and obtain power and control in social relations, promoting positive identity formation. The use of grounded theory methodology enables a full examination of Marcelo's experiences and the fundamental mechanisms guiding the development of his identity. This research deepens our comprehension of identity construction under the setting of autism, advancing both theoretical understanding and useful interventions for autistic adolescents.